Tradução em tempo real de cinemática no comando de movimento de robôs - Kassio Maciel Kienitz (2023)
The purpose of this work is to develop a real-time translation system for kinematic solutions. A case study is conducted on the translation of a Cartesian kinematic to the kinematic of a hybrid parallel robot with a serial extension. The relevance of this work lies in the fact that numerical control systems are based on Cartesian architecture machines. For the command of non-Cartesian robots, it is necessary to translate the motion commands from Cartesian space to joint space, leading to the need for changes in the control software programming. The real-time translation system acts on the motion setpoint, enabling CNCs to be used as motion controllers for robots with more complex geometries without loss of features. The hybrid geometry of the studied robot consists of a four-bar planar parallel robot in a pantographic configuration. Then, a third serial link is coupled to this closed chain of rotary joints, forming an open chain at its end. The robot’s actuation is entirely concentric at its base, and its tool moves in the XY plane, with its tool orientation over the Z-axis rotation. The kinematic solutions are found using a hybrid methodology combining the kinematic decoupling method with the K-K and D-H parametric solutions and the geometric method. Finally, a fully analytical solution is obtained for the robot’s configurations. The translation system was implemented in a simulated model developed in GNU Octave so that the parameters could be studied in a controlled environment. The DoE methodology, design of experiment, was used to develop a multifactorial experiment to study the interactions between the parameters of interest of the mathematical model. After this study, its results were used to develop a real embedded application. This was done to enable testing of the translation system’s effectiveness using an existing CNC on the market, which provides motion command in the form of frequency for each Cartesian axis. The command signal is introduced into the kinematic translator, which uses the developed kinematic solutions to generate a motion set-point according to the robot’s joint space. To evaluate the effectiveness of the system, the commanded motion in Cartesian space and the translated motion applied to the robot model are compared. At the end of the development, it is concluded that it is possible to perform real-time embedded translation of the kinematics of the robot with a response that meets the expectations of a robotic system. Thus this system can be used as a tool to aid in the development and study of new robotic solutions and geometries.